Case study of a custom colored carpet tile prototype utilizing sustainable sampling. Issue 3 (2014) - ,; ,
Abstract : Purpose – The purpose of this study was to examine the process of a custom colored carpet prototype that utilized innovative and sustainable sampling techniques.Design/methodology/approach – This study adapted the prototype design process of problem definition and research; creative exploration; and implementation by LaBat and Solowski. The stages of problem definition and research and creative exploration were conducted for this study. Since only a sample of the carpet tile was developed, the implementation stage was not applicable and was replaced with an deliberation stage. The deliberation process for sustainable sampling was based on the five major performance categories of the sustainable carpet assessment standard, NSF/ASNI 140‐2007: Public Health and Environment; Energy and Energy Efficiency; Bio‐based Content, Recycled Content, and Environmentally Preferable Materials; Manufacturing; and Reclamation and End of Life Management.Findings – A third party's proprietary sustainable sampling system was employed to support experimentation with multiple colorway applications, while minimizing sample waste. A custom colored commercial carpet tile that reflects one university's unique color palette was developed in collaboration with a large carpet manufacturer.Research limitations/implications – The deliberation stage was not intended to measure or award the points for the five performance categories. Moreover, the researchers are not eligible to certify carpet products. The certifiers are reputable auditors such as Scientific Certification Systems, UL Environment and NSF International. Rather, the five major performance categories of NSF/ASNI 140‐2007 were employed as the framework for discussion.Practical implications – Although creating a custom‐colored commercial carpet tile product was a laborious and time‐consuming activity, consumers in today's society have begun to expect tailored products that meet their needs. Custom colorization provides for personalization and the support of established color palettes without the anticipated higher associated expenses incurred with a completely custom product. At universities, where the home team's colors are omnipresent and extremely meaningful to stakeholders, developing custom colored carpet tile is appropriate.Originality/value – Sustainable sampling was effectively utilized to facilitate a custom colored carpet tile prototype. This study fills a gap in the current literature since it incorporates a case study of the design of a sustainable interior product. Previously, few studies have tracked the inception and development of a carpet product through its design phases.